1993
DOI: 10.1002/cne.903370410
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin: Cellular localization of a major phosphoprotein in the adult rat and human CNS

Abstract: Stathmin is a ubiquitous, 19 kDa cytoplasmic protein the phosphorylation of which is associated with many cellular signaling pathways. It is particularly abundant in neurons and reaches a peak of expression in the neonatal period, although it remains highly expressed in the adult brain. In order to determine whether this abundant expression is associated with discrete cellular populations that are still at an immature stage during adulthood, as suggested by others, the cellular localization of stathmin was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 47 publications
0
42
2
Order By: Relevance
“…Slides were examined in a blinded manner, and proliferation was quantified by counting the number of stathmin-and PCNA-positive cells/100 cells counted in an average of five highpower fields (ϫ40) in each section. Stathmin is a ubiquitously expressed cytosolic phosphoprotein (25,28) that has been identified as a marker of cell proliferation in the recovery phase of acute ischemic renal failure (36). Increased expression of stathmin is associated with the reentry of cells into the cell cycle and the onset of cell proliferation (7), whereas PCNA labels proliferating nuclei.…”
Section: Proliferation Assaysmentioning
confidence: 99%
“…Slides were examined in a blinded manner, and proliferation was quantified by counting the number of stathmin-and PCNA-positive cells/100 cells counted in an average of five highpower fields (ϫ40) in each section. Stathmin is a ubiquitously expressed cytosolic phosphoprotein (25,28) that has been identified as a marker of cell proliferation in the recovery phase of acute ischemic renal failure (36). Increased expression of stathmin is associated with the reentry of cells into the cell cycle and the onset of cell proliferation (7), whereas PCNA labels proliferating nuclei.…”
Section: Proliferation Assaysmentioning
confidence: 99%
“…Western blot analyses were performed as previously described by Peschanski et al (42). Briefly, 50 g of protein from each extract were loaded onto an SDS-12% polyacrylamide gel.…”
Section: Western Blot Analysis Of Stathmin Expressionmentioning
confidence: 99%
“…After two 10-min washes in 2.5% dry milk in TTBS and two 10-min washes in TBS, the membrane was developed by using peroxidase detection reagents (ECL kit; Amersham, Piscataway, NJ) and exposed for 5-30 s to an X-ray film. The stathmin antibody is highly specific and detects the stathmin as an ϳ19-kDa band (42).…”
Section: Western Blot Analysis Of Stathmin Expressionmentioning
confidence: 99%
“…It was originally identified as a cytosolic phosphoprotein in neuroendocrine cells (Sobel and Tashjian, 1983;Schubart, 1988), also called Op18 (Hailat et al, 1990) and p19 (Pasmantier et al, 1986), and then identified in high abundance in the developing brain (Schubart et al, 1989;Koppel et al, 1990;Amat et al, 1991). In the adult brain, stathmin has been detected in germinal areas with neurogenic and gliogenic potential (Amat et al, 1991) and in specific subpopulations of neurons (Peschanski et al, 1993;Camoletto et al, 1997;Ozon et al, 1999), although its expression in neurons is much lower than SCG10 (Himi et al, 1994).…”
Section: Introductionmentioning
confidence: 99%